The Influence Of Leadership Style On Employee Performance At PT. Suracojaya Abadimotor, Daya Bumi Tamalanrea Permai (BTP) Branch, Makassar City - Reinaldy Ericson Pasangka; Anwar; Burhanuddin (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to analyze the influence of leadership style on employee performance at PT. Suracojaya Abadimotor, Daya Bumi Tamalanrea Permai (BTP) Branch, Makassar City. The problem of this study began with the fluctuation of employee performance, which indicated less than optimal implementation of leadership style in the company environment. The method of research employed is a quantitative approach, utilizing a descriptive type of research. The population in this study amounted to 30 employees, and all of them were sampled through a saturated sampling technique. Data were collected through questionnaires, observations, and interviews, and analyzed using simple linear regression with the help of partial tests (t-tests). The findings indicated that the leadership style positively and significantly influenced employee performance, with a significance value of 0.001 (less than 0.05). The coefficient of determination (R²) value of 0.330 indicates that leadership style contributed 33% to improving employee performance, while the remaining 67% was influenced by other factors outside this study. These findings indicate that the leader's ability to communicate, provide direction, and build harmonious working relationships is are dominant factor that can enhance employee productivity. Thus, the better the implementation of the leadership style, the better the employee performance.